The New Public Management and gender equality policies in Universities - Cecilia Castaño Collado (Investigaciones Feministas, 2016)
Gender equality policies at European universities have been introduced in the context of reforms of higher education aimed at the implementation of market logic in the management of higher education (New Public Management). Greater transparency and mechanisms of competitiveness could call into question the traditional systems of production and reproduction of male power in universities. This article analyzes the experience of some countries that have preceded Spain in the implementation of equality policies in parallel with policies of transparency and competitiveness. Our goal is to draw conclusions that are useful for public policy.